2008
DOI: 10.1002/aqc.981
|View full text |Cite
|
Sign up to set email alerts
|

Willow (Salix spp.) and aspen (Populus tremula) regrowth after felling by the Eurasian beaver (Castor fiber): implications for riparian woodland conservation in Scotland

Abstract: ABSTRACT1. A proposed trial reintroduction of the Eurasian beaver (Castor fiber L.) to Scotland has recently been approved (May 2008). A previous proposal was turned down by the licensing authority, partly over the perceived risks to woodland within a Special Area of Conservation.2. This paper presents data on two years of willow (Salix spp.) and aspen (Populus tremula L.) regrowth following tree felling by captive beavers within two large semi-natural enclosures in eastern Scotland. Both willow and aspen are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 42 publications
1
23
0
1
Order By: Relevance
“…More beavers are expected to result in more beaver browse of willows which in turn would result in a greater impact on the asexual reproduction of willows. Jones et al (2008) observed that 35% -40% of beaver-felled willows in Scotland showed regrowth. The proportion of stems showing regrowth was variable by habitat (stream and lake) and year (Jones et al 2008).…”
Section: Asexual Reproductionmentioning
confidence: 99%
See 4 more Smart Citations
“…More beavers are expected to result in more beaver browse of willows which in turn would result in a greater impact on the asexual reproduction of willows. Jones et al (2008) observed that 35% -40% of beaver-felled willows in Scotland showed regrowth. The proportion of stems showing regrowth was variable by habitat (stream and lake) and year (Jones et al 2008).…”
Section: Asexual Reproductionmentioning
confidence: 99%
“…Jones et al (2008) observed that 35% -40% of beaver-felled willows in Scotland showed regrowth. The proportion of stems showing regrowth was variable by habitat (stream and lake) and year (Jones et al 2008). In central British Columbia 0% to 51% of beaver felled S. sitchensis showed levels of regrowth.…”
Section: Asexual Reproductionmentioning
confidence: 99%
See 3 more Smart Citations